373 TRENDS IN ADULT HEPATITIS B VACCINATION STATUS: IMPROVEMENT OR COHORT EFFECT?. Issue 1 (1st January 2007) - Koya, D. L.; Hill, E. G.; Darden, P. M.
Abstract : Background: Hepatitis B vaccination of infants and adolescents has been successful in the United States. The trends in adult immunization are not as clear. Objective: To determine the trends in hepatitis B vaccination prevalence among high-risk adults across the years 2000, 2002, and 2004. To examine the effect of age on these trends and the factors associated with vaccination receipt. Methods: We used National Health Interview Survey (NHIS) 2000, 2002, and 2004 data to examine the trends in hepatitis B vaccination coverage among adults, 18 to 49 years of age, with self-reported high-risk behaviors. Health care workers were not included. Subgroup analyses within age groups (18-29, 30-39, 40-49) by survey year were conducted to assess the vaccination prevalence status by age groups across 3 survey years. Factors independently associated with vaccination receipt were determined by a multivariate model fitted to the 3 years of data. SUDAAN was used for statistical analysis to account for the NHIS complex survey design. Results: There was a significant increasing trend in the prevalence of vaccination status across the 3 survey years (2000 = 32.6%; 2002 = 35.3%; 2004 = 41.4%; trend test p = .001). When examined by age groups, the increase in vaccination was significant only in the 18 to 29 years age group (2004 vs 2000; 52.7% vs 41.4%; p = .02). Compared with the year 2000, the 18 to 29 years age group was more likely to be vaccinated in the year 2004 after adjusting for relevant confounders (OR 1.73, 95% CI 1.14-2.6), and there was no significant increase in odds of vaccination for other age groups (30-39 and 40-49 years) between the years 2000 and 2004. The independent predictors of vaccination are survey year, age, education status, receipt of influenza or pneumococcal vaccination, and testing for HIV. An inverse association was noted between age and odds of vaccination (OR [CI] for 18-20, 21-25, 26-30, 31-40, 41-49 age strata are 4.61 [2.87-7.41], 3.02 [2.14-4.27[, 2.07 [1.45-2.96], 1.42 [1.06-1.91], 1.00, respectively). Conclusions: There was a significant trend toward higher hepatitis B vaccination status with time among high-risk adults. This trend, significant only in the younger age group, suggests a 'cohort effect' caused by successfully vaccinated adolescents reaching young adulthood. Successful strategies should be developed and implemented to improve hepatitis B immunization rates among high-risk adults, particularly among older adults, to achieve the goal of successful elimination of hepatitis B from the United States.